The Impact of Authentic Leadership on Workplace Spirituality Analytical Study of the Opinions of Academic Staff in International Universities in the Kurdistan Region of Iraq - Sardar Sabri Othman; Jalal Abdalla Muhamed; Range Mohamed Nori (Zanco Journal of Humanity Sciences)
The focus of this study was to investigate the impact of authentic leadership on workplace spirituality among academic staff at international universities. A quantitative technique (questionnaires) was used to collect data from 170 academic staff from six out of seven international universities. The results of this study indicate that authentic leadership has an important role in creating spirituality in the workplace. The results also confirmed that there is a significant correlation between the dimensions of authentic leadership (Relational Transparency, Internal Moral Perspective, Self-Awarenes, and Balance Processing), with workplace spirituality as a whole, and its Self-Awareness has the strongest correlation with workplace spirituality. Furthermore, the research shows that the impact of authentic leadership and its dimensions on workplace spirituality among academic staff statistically is significant, and among the dimensions of authentic leadership Self-Awareness has the greatest influence on the existence of spirituality in the workplace.  Finally, future qualitative studies are needed to provide deeper insight.